A Critical Appraisal of the Social Norms Approach as an Interventional Strategy for Health-Related Behavior and Attitude Change - Dempsey, Robert C.; McAlaney, John; Bewick, Bridgette M. (Frontiers in Psychology, 2018)
The Social Norms Approach is a widely used intervention strategy for promoting positive health-related behaviours. The Approach operates on the premise that individuals misperceive their peers’ behaviours and attitudes, with evidence of under- and over-estimations of behaviours and peer approval for a range of positive and negative behaviours respectively. The greater these misperceptions, the more likely an individual is to engage in negative behaviours such as consuming heavier amounts of alcohol and other substances and reduce positive behaviours such as eating healthily and using sun protection. However, there are many complexities associated with the use of social norms feedback in interventions and empirical studies. Many social norms interventions do not attempt to change misperceptions of social norms or measure changes in normative perceptions pre- and post-intervention. This has led to a conflation of generic social norms interventions with those that are explicitly testing the Approach’s assumptions that it is misperceptions of peer norms which drive behaviour. The aim of the present review was to provide a critical appraisal of the use of the Social Norms Approach as an intervention strategy for health-related behaviours, identify the current issues with its evidence base, highlight key opportunities and challenges facing the approach, and make recommendations for good practice when using the approach. There are three core challenges and areas for improved practice when using the Social Norms Approach. Firstly, improvements in the methodological rigour and clarity of reporting of ‘social norms’ research, ensuring that studies are testing the approach’s assumption of the role of misperceptions on behaviours are differentiated from studies investigating other forms of ‘social norms’. Secondly, the need for a more explicit, unified and testable theoretical model outlining the development of normative misperceptions which can be translated into interventional studies. Finally, a need for a more robust evaluation of social norms interventions in addition to randomised controlled trials, such as the inclusion of process evaluations, qualitative studies of participant experiences of social norms feedback, and alternative study designs better suited for real-world public health settings. Such improvements are required to ensure that the Social Norms Approach is adequately tested and evaluated.